MODEL PERILAKU AKUNTAN DALAM ERA REVOLUSI INDUSTRI 4.0 DAN SITUASI PHYSICAL DISTANCING (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK JAWA TENGAH) - Yulianti Yulianti; Risti Ulfi Hanifah; Ahmad Sahri Romadon (BBM (Buletin Bisnis & Manajemen), 2021)
This research is a model of accountant behavior in the era of the industrial revolution 4.0 and the physical distancing situation (empirical study at the Central Java public accounting firm). The data used are primary data by distributing questionnaires to auditors. The population in this study were accountants who worked as auditors at the Public Accounting Firm in Central Java with a sample of 123 auditors who did Work From Home (WFH). The analytical tool used in this study is multiple linear regression which is used to see indicators of the industrial revolution 4.0 and physical distancing regarding accountants' behavior models. Data was processed with the help of SPSS for Windows software. The results showed that the era of the industrial revolution 4.0 affected the behavior of accountants, by following the development of information technology, accountants tended to utilize and use paperless which became the basis for making economic decisions. Physical distancing has no effect on accountants 'behavior, this indicates that by implementing physical distancing, accountants' behavior tends to be limited in doing standard field work.